Comparison of Two Strategies for Prophylactic Donor Lymphocyte Infusion in Patients With Refractory/Relapsed Acute Leukemia - Su, Qiongqiong; Fan, Zhiping; Huang, Fen; Xu, Na; Nie, Danian; Lin, Dongjun; Guo, Ziwen; Shi, Pengcheng; Wang, Zhixiang; Jiang, Ling; Sun, Jing; Jiang, Zujun; et al. (Frontiers in Oncology, 2021)
Prophylactic donor lymphocyte infusion (pDLI) could reduce relapse in patients with refractory/relapsed acute leukemia (RRAL) undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT), but optimal timing of pDLI remains uncertain. We compared the outcomes of two strategies for pDLI based on time from transplant and minimal residual disease (MRD) status in patients with RRAL. For patients without grade II-IV acute graft-versus-host disease (aGVHD) on day +60, pDLI was given on day +60 regardless of MRD in cohort 1, and was given on day +90 unless MRD was positive on day +60 in cohort 2. A total of 161 patients with RRAL were enrolled, including 83 in cohort 1 and 78 in cohort 2. The extensive chronic GVHD (cGVHD) incidence in cohort 2 was lower than that in cohort 1 (10.3% vs. 27.9%, P=0.006) and GVHD-free/relapse-free survival (GRFS) in cohort 2 was superior to that in cohort 1 (55.1% vs. 41.0%, P=0.042). The 2-year relapse rate, overall and leukemia-free survival were comparable between the two cohorts (29.0% vs. 28.2%, P=0.986; 63.9% vs. 64.1%, P=0.863; 57.8% vs. 61.5%, P=0.666). Delaying pDLI to day +90 based on MRD for patients with RRAL undergoing allo-HSCT could lower extensive cGVHD incidence and improve GRFS without increasing incidence of leukemia relapse compared with pDLI on day +60.